The impact of the EU procurement rules on corporate responsibility in the supply chain: a study of utilities - Aspey, Eleanor (2012)
Corporate social responsibility (CSR) refers to the voluntary integration of social and environmental concerns into business practice. It is of increasing importance to utilities, with commercial pressure to be socially responsible coming from, inter alia, consumers, investors and employees. One way in which utilities can integrate CSR into their business is in their procurement. However, the potential scope for the inclusion of CSR considerations in procurement regulated by the EU is uncertain, with some policies clearly restricted but the legality of others being less clear.